Pengenalan Aplikasi Pembuatan Flowchart (RAPTOR) untuk Menunjang Pembelajaran Informatika Kelas X-11 SMA Ibrahimy Sukorejo Situbondo - Zaehol Fatah; Ritma Aulia Anjumilah (Universitas Pahlawan Tuanku Tambusai, 2026)
Grasping algorithms and flowcharts is a crucial element of the informatics curriculum, but students frequently find it difficult to understand through theoretical teaching alone. This activity intends to present the RAPTOR application as an effective tool for students in grade X-11 at SMA Ibrahimy Sukorejo Situbondo. The program was executed via an educational seminar that included interactive demonstrations. The phases involved clarifying fundamental logic programming ideas, demonstrating flowchart development with RAPTOR, and holding QA sessions to enhance participants' comprehension. Results: The seminar effectively enhanced student focus and enthusiasm for programming. By means of the visual representations shown in the session, students grasped how logical instructions function in a systematic manner. Participants displayed great excitement as they observed their flowcharts being implemented directly in the app. The spread of RAPTOR via a seminar format demonstrated to be a successful first step in encouraging students to delve into information technology in a deeper and more practical way.